All‐Electric Spin Device Operation Using the Weyl Semimetal, WTe2, at Room Temperature. (18th October 2022) - Ohnishi, Kosuke; Aoki, Motomi; Ohshima, Ryo; Shigematsu, Ei; Ando, Yuichiro; Takenobu, Taishi; Shiraishi, Masashi
Abstract: Topological quantum materials (TQMs) possess abundant and attractive spin physics, and a Weyl semimetal is the representative material because of the generation of spin polarization that is available for spin devices due to its Weyl nature. Meanwhile, a Weyl semimetal allows the other but unexplored spin polarization due to local symmetry breaking. Here, all‐electric spin device operation using a type‐II Weyl semimetal, WTe2, at room temperature is reported. The polarization of spins propagating in the all‐electric device is perpendicular to the WTe2 plane, which is ascribed to local in‐plane symmetry breaking in WTe2, yielding the spin polarization creation of propagating charged carriers, namely, the spin‐polarized state creation from the nonpolarized state. Systematic control experiments unequivocally negate unexpected artifacts, such as the anomalous Hall effect, the anisotropic magnetoresistance, etc. Creation of all‐electric spin devices made of TQMs and their operation at room temperature can pave a new pathway for novel spin devices made of TQMs resilient to thermal fluctuation. Abstract : All‐electric spin device operation using a type‐II Weyl semimetal, WTe2, at room temperature is achieved. The polarization of spins propagating in the all‐electric device is perpendicular to the WTe2 plane, which is ascribed to local in‐plane symmetry breaking in WTe2, yielding the spin polarization creation of propagating charged carriers, namely, the spin‐polarized state creation from the nonpolarized state. Creation of all‐electric spin devices made of topological quantum materials (TQMs) and their operation at room temperature can pave a new pathway for novel spin devices made of TQMs resilient to thermal fluctuation.